Manowce polskiej egiptologii XIX wieku. II. Szczęsny Morawski i jego „studia” nad starożytnym Egiptem - Kaczmarek, Hieronim (Folia Praehistorica Posnaniensia, 2018)
The article is a part of larger publication under preparation, which is intended to address acquaintance with ancient Egypt in Poland at the beginning of the 20,h century. In particular, it presents ‘research attempts’ of Szczęsny Morawski (1881-1898) concerning a supposed Phoenician genesis of the Slavs and the Egyptian-Phoenician occupation of the Polish lands in antiquity.